Cerebral Blood Flow and Cerebrovascular Reactivity Measurement using Arterial Spin Labeling MRI: Data from The Irish Longitudinal Study on Ageing (TILDA) - Ní Leidhin, Caoilfhionn (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2022)
Background: Cerebral blood flow (CBF) and cerebrovascular reactivity (CVR) are important measures of cerebrovascular integrity and may provide an imaging biomarker for the early detection of diseases such as dementia and stroke. However, differentiating normal age-related decline in cerebral perfusion from pathological reduction has been hampered by the lack of reference values. Methods: The study cohort comprised a subset of nationally representative, neurologically asymptomatic, community dwellers aged 50 years and older enrolled in TILDA. Grey matter (GM) cerebral perfusion was measured using pcASL MRI at 3 Tesla. Data from 468 of 578 subjects attending for MRI were used for CBF analysis. Normative cerebral perfusion values were estimated using Generalized Additive Models for Location Shape and Scale. A subset of 148 participants also attempted a hypercapnic challenge to assess CVR. Data from 104 subjects were used for CVR analysis. Results: Mean age of the baseline/normocapnic cohort was 68.2 ± 6.9 years. 51.7% were female. Mean CBFGM was 36.5 ± 8.2 ml/100g/min. CBFGM decreased by 0.2 ml/100g/min per year increase in age (95% CI = -0.28, -0.08, p  0.001) and was 3.1 ml/100g/min higher in females (95% CI = 1.64, 4.54, p  0.001). CBFGM decreased by 0.3 ml/100g/min per 1 unit increase in body mass index (BMI) (95% CI = -0.51, -0.18, p  0.001) and by 0.1 ml/100g/min per 1 mmHg increase in mean systolic (95% CI = -0.10, -0.03, p ≤ 0.001), diastolic (95% CI = -0.20, -0.07, p ≤ 0.001) and mean arterial (95% CI = -0.17, -0.06, p ≤ 0.001) blood pressures (BP) respectively. Mean age of the hypercapnic challenge cohort was 67.3 ± 6.4 years. 49.0% were female. CBFGM increased with the administration of carbon dioxide from 37.2 ± 7.8 to 49.9 ± 10.8 ml/100g/min. Mean percentage change between normo- and hypercapnia was 35.2 ± 16.2%. Mean CVRGM was 2.4 ± 1.2. There was no statistically significant relationship between CVRGM and age or sex. CVRGM increased by 0.1 per 1 unit increase in BMI (95% CI = 0.02, 0.12, p ≤ 0.007). Conclusions: This study is the largest to present normative reference values for CBFGM measured using 3T pcASL MRI in an ageing cohort. Significant age- and sex-related differences were observed in CBFGM, thus these factors need to be accounted for when studying brain perfusion. This research also demonstrated significant associations between cardiovascular risk factors such as BMI/BP and CBF/CVR, thereby potentially providing a biomarker for intervention in those at risk of dementia and stroke due to altered cerebral haemodynamics.
APPROVED
Keywords: The Irish Longitudinal Study on Ageing; Cerebrovascular Reactivity; Cerebral Blood Flow; Magnetic Resonance Imaging; Arterial Spin Labeling